Screening Salicylate Production In Line 15 Plants Of Transgenic Tobacco Overexpressevg Microbial Genes For Salicylate Biosynthesis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The activity of isochorismate synthase (ICS) and isochorismate pyruvate lyase (IPL) obtained by measuring isochorismate and salycilic acid (SA) formed after incubation of the protein extracts with chorismate were carried out in 20 plants of constitutively producing salicylic acid (CS A) tobacco line 15. The total SA in free and bound form was also detected. The results show that there is no relationship between the ICS and IPL activity in the various plants. The activity of IPL is clearly the SA production determining step, with for example two plants with highest SA levels but lowest total isochorismate produced in the in vitro incubation. The plants with high IPL activity thus have high SA content.